Framing Respons Hasan Nasbi Kasus Kepala Babi Tempo di Detik.com dan Kompas.com - Hidayah, Rofi; Adiyanto, Wiwid (Jurnal Ilmu Komunikasi, 2026)
The case of sending a package of pig heads to Tempo journalists on March 19, 2025, sparked widespread attention, particularly after the response of the Head of the Presidential Communications Office, Hasan Nasbi, was deemed to lack empathy. This study aims to examine the framing of Detik.com and Kompas.com regarding this response in the context of terror against journalists and government public communication. The research uses a descriptive qualitative approach with Pan and Kosicki's framing analysis of 14 news articles published between March 19 and April 9, 2025. The findings show that Detik.com presents the issue dynamically by including government clarifications as well as political and ethical criticism, thus highlighting the polemic of elite communication. In contrast, Kompas.com emphasizes the issue of press freedom and the chronology of events at the beginning of the report, then directs the narrative to the government's internal evaluation through the President's acknowledgment of responsibility. Differences in structure and choice of diction demonstrate the media's role in shaping meaning and influencing public perceptions of press terror, state accountability, and the quality of democratic communication.